Fenomena Peradilan Rakyat dalam Perspektif Pemberlakuan Syari'at Islam di Aceh - Rusjdi Ali Muhammad (Islam Futura, 2001)
Among the most significant impact of the ongoing conflict in Aceh is the weakening of law enforcement in society. Indeed, thius result is emergence of what is known as ‘people court” (pengadilan rakyat). According to the information provided by the Human Rights Commission of Aceh Branch (FP HAM), there were at least eighteen cases of people court that took place in the region within the period between September 1999 and January 2001. Indeed, this is an interesting phenomenon to be studied, especially when it is seen from Islamic legal perspective. As it is known, in Islam both formal and informal institutions are to play their significant roles in maintaining law and moral order, a concept discussed under the topic of wilayat al-tahkim. However, this study shows that the Acehnese cases are indeed far from the Islamic judicial system.